2022
DOI: 10.1007/s00227-021-04008-5
|View full text |Cite
|
Sign up to set email alerts
|

The range expansion of Clibanarius erythropus to the UK suggests that other range-shifting intertidal species may not follow

Abstract: The ranges of species are shifting as a consequence of anthropogenic climate change. In the marine realm biogeographic transition zones could form barriers to dispersal and inhibit range-shift, but little is known about this potential effect. The hermit crab Clibanarius erythropus appeared in the UK in 2016 with the nearest reproducing population being on the northern coast of Brittany. This raises questions of which conditions may have permitted C. erythropus to cross the English Channel (7.25°W, 49.00°N) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The first hypothesis involves the migration of the species from Africa to Europe, a process known as tropicalization (Cuesta et al, 2016). It is well known that anthropogenic activities and climate change are among the most important factors that may enhance the establishment of introduced species, as well as the poleward shift in distribution of numerous species over decades (González‐Ortegón et al, 2020), even overcoming important geographic barriers under favorable conditions (Patterson et al, 2022). The Strait of Gibraltar area has an important role as a pathway of introductions both from the Mediterranean Sea and by West African biota moving northwards into European waters, the later labeled as “African Creep” by Canning‐Clode and Carlton (2017).…”
Section: Discussionmentioning
confidence: 99%
“…The first hypothesis involves the migration of the species from Africa to Europe, a process known as tropicalization (Cuesta et al, 2016). It is well known that anthropogenic activities and climate change are among the most important factors that may enhance the establishment of introduced species, as well as the poleward shift in distribution of numerous species over decades (González‐Ortegón et al, 2020), even overcoming important geographic barriers under favorable conditions (Patterson et al, 2022). The Strait of Gibraltar area has an important role as a pathway of introductions both from the Mediterranean Sea and by West African biota moving northwards into European waters, the later labeled as “African Creep” by Canning‐Clode and Carlton (2017).…”
Section: Discussionmentioning
confidence: 99%
“…This dispersal capacity accords with the relatively low genetic differentiation detected between these areas and is again suggestive of stepping-stone connectivity. Similarly, dispersal simulations for a species of hermit crab, Clibanarius erythropus, suggested that larval transport from Brittany, northwest France, to southwest Britain is rare but possible and results from unusual ocean currents, though the authors found the Channel may still act as a barrier to species with a larval PLD of less than 20 days (Patterson et al, 2022). Similarly, Ayata et al ( 2010) simulated particle dispersal trajectories with a 4-week PLD and showed successful dispersal across the Channel due to residual circulation under realistic hydrodynamic conditions.…”
Section: Connectivity Across the English Channelmentioning
confidence: 99%